The Efficacy of Hydrodilatation for the Prevention of Vasospasm following Microsurgical Anastomosis - BAYRAMİÇLİ, MEHMET NURİ ÜMİT; KAYA, ÖZLEM TUĞÇE; AKDENİZ DOĞAN, ZEYNEP DENİZ (THIEME MEDICAL PUBL INC, 2022)
Introduction Vasospasm is a major problem following microsurgical reconstruction which can result in the partial or complete loss of the flap tissue. The aim of this study was to investigate the efficiency of hydrodilatation for the prevention of vasospasm. Material and Methods Thirty male Wistar rats were used for this experimental study. Femoral arteries of were exposed, photographed, and transected. In group 1, group 2, and group 3 papaverine solution, hydrodilatation, and minimal mechanical dilatation (control group) was performed, respectively. The anastomosis was completed and the arteries were photographed again 10minutes after completion of the anastomosis. Following 7-day period samples for transmission electron microscopy (TEM) and light microscopy were obtained. Results The mean vessel diameters prior to transection were 0.43, 0.45, and 0.52mm in the papaverine, hydrodilatation, and control groups, respectively. The mean vessel diameter 10minutes following the completion of anastomosis was 0.76, 0.75, and 0.51mm in the papaverine, hydrodilatation, and control groups, respectively. Median score for papaverine group regarding histological parameters of regular endothelial lining and lumen, neutrophil infiltration, vascular congestion, and edema in tunica adventitia was 2, 3, 2, and 3 positive, respectively. Median score for the papaverine group regarding histological parameters of regular endothelial lining and lumen, neutrophil infiltration, vascular congestion, and edema in tunica adventitia was 3, 3, 3, and 3 positive, respectively. All the histological scores were negative in the control group. The difference between the control group and the experiment groups 1 and 2 was significant regarding all four histological parameters ( p <0.05). Conclusion Hydrodilatation and papaverine application were both effective in preventing vasospasm following microsurgical intervention but papaverine caused slightly less damage to the endothelial lining and less edema in the tunica adventitia when compared with the hydrodilatation. Hydrodilatation group showed a vasodilatory effect that was statistically similar to that of papaverine, which has a proven efficacy.
Keywords: vasospasm; hydrodilatation; microsurgery; supermicrosurgery; DRUG-INDUCED VASODILATION; MICROVASCULAR ANASTOMOSIS; IN-VITRO; PAPAVERINE; LIDOCAINE; ARTERY; VIVO; FLAP